ANALISIS PENGARUH TATA KELOLA PERUSAHAAN DAN STRUKTUR KEPEMILIKAN TERHADAP STRUKTUR MODAL (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2017) - Giovanni Osvald Eko Prasetyo; Paulus Th Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2019)
This study aims to analyze affect of coorporate governance and ownership structure toward capital structure of financial reports to the manufacturing companies with control variables firm size and asset tangibility. Capital structure is proxied by Debt to Asset Ratio (DAR) as a measure of financial performance based on the company’s operations. The examined factors of this research are outside director, board size, audit committee size, managerial ownership and institutional ownership as the independent variables while firm size,asset tangibility and profitability as control variables.The sample in this research were manufacturing companies listed in Indonesian Stock Exchange (IDX) in the period 2015-2017. The number of sample used were 43 companies listed were taken by purposive sampling. The method of analysis of this research used multiple liniear regression. The result of this research shows that institutional ownership has a positive significant effect toward capital structure, board size has a negative significant effect toward capital structure. Meanwhile variable outside director, audit comittee size and managerial ownership have no significant effect toward capital structure. This research also find that the control variables which are profitability have significant and negative effect to capital structure and for the firm size and asset tangibility have not significant effect